Meteorological factors associated with hand, foot and mouth disease in a Central Highlands province in Viet Nam: an ecological study - Hau Van Pham; Uyen Thi Ngoc Phan; Anh Nguyen Quynh Pham (World Health Organization Regional Office for the Western Pacific, 2019)
Background: Hand, foot and mouth disease (HFMD) is a public health problem in Viet Nam, and studies have reported seasonal fluctuation in the occurrence of HFMD. This study sought to describe the occurrence of HFMD and its associated meteorological factors in Dak Lak province, Viet Nam. Methods: Monthly data on HFMD cases were collected from all commune health stations in Dak Lak province from 2012 through 2013. An HFMD case was defined as a brief febrile illness accompanied by a typical skin rash with or without mouth ulcers. Average temperature, maximum temperature, minimum temperature, humidity, rainfall, evaporation, sunshine duration and wind speed were recorded monthly at five local meteorological stations throughout Dak Lak.Data were aggregated at the district level, and the association between these meteorological factors and HFMD cases were examined by Poisson regression. Results: In 2012 through 2013, there were 7128 HFMD patients in Dak Lak. The number of HFMD cases increased during the rainy season. An increased risk of HFMD was associated with higher average temperature (risk ratio and 95% confidence interval: 1.06; 1.03-1.08 per 1 °C increase), higher rainfall (1.19; 1.14-1.24 per 200 mm increase) and longer sunshine duration (1.14; 1.07-1.22 per 60 hours increase). The risk of HFMD was inversely associated with wind speed (0.77; 0.73-0.81 per 1 m/s increase). Conclusion: This study suggests that there is a significant association between HFMD occurrence and climate. Temperature, rainfall, wind speed and sunshine duration could be used as meteorological predictors of HFMD occurrence in Viet Nam's Central Highlands region. Intensified surveillance for HFMD during the rainy season is recommended.